Demographics: a world failover or several regional failovers? - (:unkn) unknown (My University, 2013)
According to the average demographic outlook 2025, the population of Asia will remain the majority in the world. But tilting the Atlantic world to the Pacific is less demographic and economic. In demographic terms, failover may be more African than Asian. Another surprise could come from America, as a result of the sharp decline in fertility in the South and a growth driven by a continued strong migration attraction in the North.
Keywords: African Research